(untitled) (Nepalese Veterinary Journal, 2023)
Tuberculosis (TB) is an infectious zoonotic disease, characterized by the development of tubercles resulting in caseation and calcification in the lungs. In elephants, causative agents Mycobacterium tuberculosis and Mycobacterium bovis result in chronic weight loss, anorexia, and weakness with occasional dyspnea or coughing. TB has been a major threat to elephants in Nepal. To date, 17 elephants have died in Nepal due to TB alone. Therefore, this study was undertaken to screen the TB seropositive elephants in Nepal. A cross-sectional study was conducted to determine the seroprevalence of tuberculosis (TB) in captive Asian elephants in four protected areas of Nepal from 22 November 2015 to 17 April 2016. The serum samples were examined for tubercle bacillus antibodies by DPP Vet TB Assay. Out of 92 elephants, 10.87% of elephants were found reactive to the bacterium Mycobacterium tuberculosis complex. There was a non-significant difference in seroprevalence of TB in captive Asian elephants for the sex, age, and location (P>0.05). In a follow-up study, we found that 4 TB seropositive elephants from our study died due to TB and displayed granulomatous tuberculosis lesions with the caseous mass in the lungs on post-mortem examination. Government and non-government stakeholders should jointly formulate effective plans and policies to eradicate tuberculosis from elephants in Nepal.